The Mediating Role of Trust in the Influence of Influencer Credibility and Shopping Experience on Repurchase Intention E-commerce - Fitri, Nurul Amalia; Lastri, Surna; Erlinda, Erlinda; Murhadi, Thasrif (Budapest International Research and Critics University, 2025)
The role of trust is becoming increasingly important in building consumer loyalty in the competitive e-commerce era. This study aims to analyze the role of trust mediation in the relationship between influencer credibility and shopping experience on repurchase intention in e-commerce. The study uses a quantitative approach with the variables of influencer credibility, shopping experience, trust, and repurchase intention. Data was collected through a questionnaire from 397 students from seven universities in Banda Aceh with the criteria of having made a transaction on the Shopee platform, as a representation of one of the largest e-commerce in Indonesia. Data analysis was carried out using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that influencer credibility and shopping experience had a positive effect on trust, and trust mediated the influence of both on repurchase intent. These findings confirm that trust is a key factor in increasing consumer loyalty in e-commerce. Practically, the study emphasizes the importance of building influencer credibility and creating a positive shopping experience to encourage repurchases. The originality of the research lies in its focus on students as a segment of potential consumers by placing trust as a mediating variable in the context of e-commerce.